Perlindungan Hukum terhadap Saksi dalam Perkara Pidana di Pengadilan Negeri Palopo - Panji Jawoto; Hisma Kahman; Laola Subair (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study examines legal protection for witnesses in criminal cases at the Palopo District Court, focusing on witness examination procedures during trials and challenges in narcotics and domestic violence (KDRT) cases. An empirical juridical approach was employed, with data collected via judge interviews, courtroom observations, and analysis of legal documents based on the Criminal Procedure Code (KUHAP, 2025 revision), Law No. 13/2006 jo. Law No. 31/2014, and Law No. 23/2004. Findings reveal that witness testimonies, expert opinions, documentary evidence, and indicative evidence are effective, despite obstacles such as syndicate threats, long geographical distances, physical/psychological trauma, and suboptimal LPSK responses. Implementation of KUHAP Articles 160–183 and 188 is flexible at the Palopo District Court, but South Sulawesi's social pressures and infrastructural limitations undermine the two valid evidence minimum principle (Article 183 KUHAP). Witness protection is partially successful; inter-agency coordination, document standardization, and apparatus training must be stregngthened for proportional judicial decisions. Expedite LPSK interventions, robust virtual trials, and mobile forensic medical services.